Success of Pilot Grant Program leads to Funding by Robert Saligman Charitable Foundation (Jefferson Digital Commons, 2017)
In 2016, the Department of Surgery launched the Support of Surgery Research Activities Pilot Grant Program. In the first year alone, six projects were approved and funded. Recognizing the importance of innovative research and the success of this funding model, the Robert Saligman Charitable Foundation made a generous contribution in June 2017 to bolster future exploratory studies. The new Saligman Family Surgery Pilot Grant Program encourages faculty members, residents and fellows to apply for grants of up to $15,000 per year to pursue independent research programs. Here are updates from the principal investigators of three ongoing studies. “This funding mechanism is invaluable for our faculty, residents, and medical students to initiate important clinical research projects and address questions that we hope may ultimately improve patient care at Jefferson.” – Jonathan R. Brody, PhD J. Wallace Davis and Gail G. Davis Professor of Surgery Director, Division of Surgical Research Vice Chair for Research Department of Surgery _____________________________________________ Reducing colorectal surgical site infections “Several years ago, I attended an American College of Surgeons meeting and saw a poster presentation about the use of lidocaine in cholecystectomy wounds. Lidocaine either kills or stops reproduction of many bacterial organisms, and had a dramatic impact on reducing surgical site infection in cholecystectomy patients. I thought, ‘Why don’t we give that a try in colorectal cases?’ With the use of lidocaine, we found that our rate of surgical site infection declined, but we couldn’t prove how. “With this lab-based study, we have microbiologists and surgical residents, Brock Hewitt MD, MPH, and Sami Tannouri, MD, working together to explore how another local anesthetic, bupivocaine, works to prevent surgical site infections. Bupivocaine can be delivered alone or can be bound with liposomes, or fat, so that it lasts longer. “We are working to understand whether or not liposomal binding affects wound infection ...